Sistemática e ecologia de Hyalella Smith, 1874 (Crustacea, Amphipoda, Hyalellidae) no noroeste do Rio Grande do Sul, Brasil - Limberger, Marcio (2024)
The amphipods of the genus Hyalella are widely distributed throughout the Americas. However, the diversity, distribution, and ecology of this genus in Brazil remain poorly documented. In this thesis, these aspects were studied in the northwest region of the state of Rio Grande do Sul, southern Brazil. Firstly, the diversity and distribution of the genus were evaluated in an area of approximately 2776 km². Among the 488 sampled points, five already known species were identified: H. bonariensis, H. gauchensis, H. georginae, H. longipropodus, and H. palmeirensis. It was found that the distribution areas of H. bonariensis, H. gauchensis, H. longipropodus, and H. palmeirensis were expanded. Additionally, evidence was found that environmental characteristics such as aquatic vegetation, presence of livestock, and human habitation around freshwater bodies may influence the presence/absence of Hyalella. Furthermore, five unknown morphotypes were recorded. Two of these morphotypes, H. luciae and H. jaboticabensis, had their descriptions published and are presented in this work, along with Hyalella n. sp., which is described in this thesis but not yet published. Among the morphological variations found in the described species, notable characteristics include the pattern, number, and type of setae on the inner face of the propodus of gnathopod 1 in males, presence/absence of combscales on the segments of gnathopods 1 and 2, number of cuspidate setae and accessory setae on uropods 1, 2, and 3, presence and variation in length of the accessory seta on the inner ramus of uropod 1, as well as the shape, number of setae, and setation pattern on the margin of the telson. Additionally, were evaluated the population biology and reproductive aspects of Hyalella sp. nov. Collections were made monthly over a period of one year, where the size distribution did not show a normal distribution, being polymodal for males and females, and unimodal for juveniles. Pairs in pre-copulatory behavior, males, females, ovigerous females, and juveniles were observed during all seasons of the year. Males had a larger average body size than females, which were more frequent than males in the population during the sampling period. Both the formation of pairs and the presence of ovigerous females and the entry of juveniles into the population were more intense in the colder seasons of the year, indicating an important strategy to maximize success and population maintenance. Thus, this thesis contributes to the knowledge of the diversity and distribution of the genus Hyalella in the northwest region of the state of Rio Grande do Sul, as well as providing support for future taxonomy and ecology studies related to freshwater amphipods in Brazilian territory.